Nadine Gordimer: The White Artist as A Sport of Nature - Barbara Temple-Thurston (Studies in 20th & 21st Century Literature, 1991)
This article applies principles of new historicism to show that A Sport of Nature can be read as Gordimer's attempt to persuade South African artists to reject mere protest art and to shift art beyond the trap of oppositional forces in South Africa's history today. The text calls instead—via fiction and the imagination—for a new post-apartheid art that will generate creative possibilities for a future South Africa. Gordimer's protagonist, Hillela Capran, is read as a metaphor for the white South African artist who, like Hillela, struggles for an authentic identity and meaningful role in the evolving history of South Africa. This paper asserts that A Sport of Nature boldly proposes the mutation necessary for the South African artist and people to resolve the political, personal, or artistic fragmentation, beckoning other artists along the path. Hope of its assured success, however, remains as elusive and unpredictable as any "sport of nature" must be.
Keywords: new historicism; A Sport of Nature; Gordimer; South African; artists; protest art; South African history; fiction; imagination; post-apartheid; art; South Africa; Nadine Gordimer; Hillela Capran; white South African artist; white; authentic identity; identity; mutation; political; personal; artistic fragmentation; sport of nature